LASER-POLARIMETRIC DIAGNOSTICS OF THE STRUCTURAL ORGANIZATION OF THE PULMONARY TISSUE IN NORM AND PATHOLOGY - Boychuk, T.; Petryshen, A.; Chernikova, G.; Grygoryshyn, P.; Yermolenko, S. (World of Medicine and Biology, 2012)
On histological sections polarization properties of the biological tissues of respiratory system in norm and pathology were studied. Visualized polarized laser fields are presented as a superposition of the distribution of isotropic and anisotropic optical structures, defined criteria for diagnosing a pathological condition of lung tissue on the basis of statistical, correlation and fractal analysis architectonic structure of the polarized laser images.